Green Composites Sustainable Raw Materials - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology, 2019)
This book highlights the production of green composites from various sustainable raw materials. We now live in an environmentally conscious era, in which sustainable raw materials (renewable, biodegradable, recycled), sustainable processing sequences, the production of recyclable and biodegradable products, and avoiding the depletion of renewable resources are key considerations with regarding to producing any product. The textile sector is no exception. Accordingly, this book addresses these aspects in connection with textiles, and discusses how they can be actively practiced.